2022
DOI: 10.1101/gr.276207.121
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of zygotic genome activation entry and exit by H3K4me3 and H3K27me3 in porcine early embryos

Abstract: Histone modifications are critical epigenetic indicators of chromatin state associated with gene expression. Although the reprogramming patterns of H3K4me3 and H3K27me3 have been elucidated in mouse and human preimplantation embryos, the relationship between these marks and zygotic genome activation (ZGA) remains poorly understood. By ultra-low-input native chromatin immunoprecipitation and sequencing, we profiled global H3K4me3 and H3K27me3 in porcine oocytes and in vitro fertilized (IVF) embryos. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Demethylation of H3K4me3 by KDM5 proteins is crucial for proper EGA [ 9 , 12 , 16 ]. Of the KDM5 family, only lysine demethylase 5A ( KDM5A ) transcripts were detected in porcine oocytes [ 9 ]. These transcripts are stored during the oocyte growth phase [ 1 , 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Demethylation of H3K4me3 by KDM5 proteins is crucial for proper EGA [ 9 , 12 , 16 ]. Of the KDM5 family, only lysine demethylase 5A ( KDM5A ) transcripts were detected in porcine oocytes [ 9 ]. These transcripts are stored during the oocyte growth phase [ 1 , 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expression stability of five references genes, previously validated and/or utilised as reference genes in similar studies; Actin beta ( ACTB ) [ 18 , 31 33 ], glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) [ 9 , 18 , 31 , 34 ], hypoxanthine phosphoribosyltransferase 1 ( HPRT1 ) [ 35 ], tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein gamma ( YWHAG ) [ 18 ] and hydroxymethylbilane synthase ( HMBS aka PBGD ) [ 36 , 37 ], were compared employing the software program NormFinder [ 23 ]. GeNorm [ 22 ] is perhaps the most widely used algorithm for assessing reference gene stability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis of H3K4me3 enrichment in PFF and PTr2 cells revealed that the vast majority of H3K4me3 sites in both cell lines were in promoter regions around transcriptional start sites of transcriptionally active genes, an observation that is consistent with the character of this mark as reported in the literature. H3K4me3 is one of the most widely profiled histone marks and is known to be enriched around active promoters during embryonic development and beyond [ 52 57 ]. Similarly, H3K27ac showed enrichment at promoter regions, though relatively less than H3K4me3, likely due to its presence at both promoters and enhancers [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%